Tautening effect mechanism of titanium-alloy InterTAN nail - Gao, Xiang-Sheng; Ma, Sheng-Kai; Chen, Wang-Ao-Ran; Wang, Min; Pan, Qi; Liu, Zi-Yu (Rare metals, 2023)
Although InterTAN (IT) nails are widely employed to treat femoral intertrochanteric fractures, the mechanism behind the tautening effect of titanium-alloy IT nails is not well understood. This study aimed to reveal the mechanism of this effect. A torque test experiment was conducted, with the torque value recorded and transformed to obtain the tautening effect. Then, theoretical and finite element analyses were performed to further understand the mechanism. The influence of age and pitch-difference on the tautening effect was also examined in the study, the results attributed to the pitch-varying integrated interlocking lag screw. The torque and the corresponding tautening effect drastically increase as the screw is inserted deeper during the second stage, while the torque measured in the first stage is always zero. Additionally, the tautening force increases with increasing age, this relationship helps evaluate the effect at different ages. The tautening effect also increases nearly linearly with the pitch difference, which can be adjusted during the IT design stage to select or design IT in engineering practice. Graphical abstract